Multiprofessional team and integrative and complementary practices in occupational health service (Research, Society and Development, 2020)
This study aimed to describe about the application of Integrative and Complementary Practices by the multidisciplinary team in the SAST of a municipality located in the west of Santa Catarina . This is a qualitative research that used the semi-structured  interview with ten professionals of the service as a collection method. The data were analyzed using Minayo's operative proposal. Three thematic categories emerged from the analysis process : 1. The team's commitment is our differential; 2. The management of Integrative and Complementary Practices (PICs): investing in health promotion; and 3. (Re) knowledge of PICs: the importance of National Policy of Integrative and Complementary Practices. It is considered that the objectives were achieved, as the development of the work of the multidisciplinary team was evidenced, in which it stands out as a strength and as a differential. Qualified assistance is sought, in teaching and in the search for knowledge, in attention to the managerial issues and instituted norms and in the realization of education and health promotion.